Strategic entrepreneurial ecosystems and business model innovation - Ratten, Vanessa (Bingley, U.K. : Emerald Publishing Limited, 2022)
Entrepreneurial ecosystems require business model innovation as part of their evolution. This means when discussing any form of entrepreneurship that involves change, we should consider the role of business models. Strategic Entrepreneurial Ecosystems and Business Model Innovation is the first collection to focus both on entrepreneurial ecosystems and business model innovation, thereby taking a novel and new approach to entrepreneurship and strategic management. Whilst the research on entrepreneurial ecosystems is new the practice has been around for a long time. This means it is important to consider historical developments of entrepreneurial ecosystems with new trends in the form of digitalization. Recognising the need to stress the way business models have altered because of the increase in the knowledge economy, business model innovation is a useful way to consider how entrepreneurial ecosystems develop based on knowledge exchanged in the global business environment. Each chapter of this edited collection focuses on a different area of interest regarding entrepreneurial ecosystems and business model innovation, fusing the literature of both streams of thought in terms of how entrepreneurship evolves based on contextual change.
Chapter 1. Towards a theory of strategic entrepreneurial ecosystems and business model innovation / Vanessa Ratten -- Chapter 2. Unveiling the role of entrepreneurial education in preparing the next generation of entrepreneurs in Malaysia / Feranita Feranita, Roy Mouawad, Muslim Amin, Lin Woon Leong, and Thanuja Rathakrishnan -- Chapter 3. Business innovation amidst the covid-19 crisis in brunei darussalam: A viewpoint / Khairul Hidayatullah Basir -- Chapter 4. How women entrepreneurs are adapting in dynamic entrepreneurial ecosystem of pakistan / Sumayya Rashid and Vanessa Ratten -- Chapter 5. Culture, economic, and entrepreneurial environment in the gulf cooperation council (gcc) countries / Sami Alanzi, Vanessa Ratten, Clare D'Souza, and Marthin Nanere -- Chapter 6. Entrepreneurship in Spain and portugal / Mercedes Barrachina Fernández, María del Carmen García Centeno, and Carmen Calderón Patier -- Chapter 7. Evolution of entrepreneurial teams during business incubation stages / Linda Elizabeth Ruiz and Elda Barron -- Chapter 8. The role of pleasure (joy) in enhancing pre-graduate students` creativity / Alejandra Zuccoli, Hugues Seraphin, and Maximiliano Korstanje -- Chapter 9. The effect of information communication technologies on firm's innovation performance in sub-saharan African countries / Soubaneh Omar Bouh and Hülya Unlu -- Chapter 10. The msmes digital readiness in indonesia: A test of moderating effect of intrinsic motivation and ict knowledge / Rakian Abdi, Lieli Suharti, Petrus Usmanij, and Vanessa Ratten.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; Entrepreneurship; Strategic planning; Business & Economics -- Entrepreneurship; Entrepreneurship